PENGARUH KEBUTUHAN AKTUALISASI DIRI DAN KEBUTUHAN SOSIAL TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PINRANG - Leni, Suriani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
employee performance at the Office of Population and Civil Registration of Pinrang Regency. (2) the influence of social needs variables on the work performance of employees at the Office of Population and Civil Registration of Pinrang Regency. This research is categorized as survey research, where the research instrument is a questionnaire. The population in this study were employees of the Office of Population and Civil Registration of Pinrang Regency. The population in this study was 116 employees of the Population and Civil Registration Office of Pinrang Regency. The samples taken in this study were all employees with a total of 116 respondents. The instrument validity test uses the Pearson correlation approach, while the reliability test uses Cronbach Alpha. The analysis technique used is multiple linear regression. The results of this study found that (1) the need for self-actualization has a significant effect on employee performance at the Pinrang Regency Population and Civil Registration Office. (2) social needs have a significant effect on employee performance at the Pinrang Regency Population and Civil Registration Office. (3) the effect of self-actualization needs and social needs together has a significant influence on employee work performance at the Pinrang Regency Population and Civil Registration Office.